The factors of psychological well-being of adolescents with disabilities - Baranauskienė, Ingrida; Serdiuk, Liudmyla; Danyliuk,, Ivan; Kurapov, Anton (Special Education, 2019)
The article describes the psychological study aimed at determining of the factors supporting disabled adolescents’ psychological well-being. Learning in the inclusive educational environment has a high developmental potential for social adaptation, revealing of the internal resources for self-realization and psychological well-being of adolescents with disabilities. The factors supporting disabled adolescents’ psychological well-being are revealed and the prognostic model of its development is proposed. The most important factors supporting disabled adolescents’ psychological well-being are: an expected attitude from others to them, their self-interest, self-esteem, meanings in life and goals understood by them, self-confidence, and belief in their own abilities. The predictors having the greatest impact on psychological well-being and presented in the developed predictive model are: commitment, acceptance of aggression, self-esteem, and the expected attitude of others.
Keywords: psychological well-being; life satisfaction; personal growth; adolescents with disabilities; integration; inclusion